THE EFFECT OF DIFFERENT MOUNT ADDITION OF SEAWEED (Eucheuma cottonii) FLOUR TOWARD CHARACTERISTICS OF CATFISH (Pangasius hypophthalmus) NUGGET QUALITY - Raja Anita Lufhiana; Sumarto '; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was aimed to obtain the best amount of seaweed (Eucheuma cottonii) flour in processing of catfish (Pangasius hypophthalmus) nugget from organoleptic quality, folding test, and chemical analysis aspects. The experimental methode was used in this research, with treatment N0 (control), N1 (addition 50g of seaweed flour), N2 (addition 100g of seaweed flour), N3 (addition 150g of seaweed flour). Based on parameters tested, the best treatment was the catfish nuggets with addition 50g of seaweed flour. The characteristics of such a ligh brown, fish flavor more pronounced, aroma of fish, solid texture, compact, and chewy with 58,62% of moisture content, 13,92% of protein content, 7,65% of fat content, 2,15% of ash, 9,15% mg/100g calcium, and 3,6 of folding test.Keywords: Nugget, Eucheuma cottonii, Pangasius hypophthalmus, Seaweed flour, Quality